THE EFFECTIVENESS OF DISCOVERY LEARNING IN IMPROVING ENGLISH WRITING SKILL OF EXTROVERTED AND INTROVERTED STUDENTS - Daniar Sofeny (Universitas Muhammadiyah Surakarta, 2017)
This study aimed to describe the effectiveness of discovery learning in improvingEnglish writing skill of extroverted and introverted students which is compared withdirect instruction as the traditional learning method. In this research, the researcheremployed a quantitative research by using experimental factorial design. Thepopulation in this research was the eleventh graders of state senior high school Salein academic year 2013/ 2014 and the samples were 20 students from both classesand categories. The try out was conducted to measure validity and reliability. Andthe two ways ANOVA was conducted to test the hypotheses, two –way analysis ofvariance with F-test at the 5% (0.05) level of significance. The result of this studyrevealed that the use of discovery learning was effective to the extroverted studentsthan the introverted students. In line with it, the finding indicates that the use of directinstruction was also effective to introverted students than the extroverted students. Inother words, the result of the used of discovery learning had a bigger influence to theextroverted students rather than introverted students.